2020
DOI: 10.1039/c9ta10284a
|View full text |Cite|
|
Sign up to set email alerts
|

l-Ascorbic acid oxygen-induced micro-electronic fields over metal-free polyimide for peroxymonosulfate activation to realize efficient multi-pathway destruction of contaminants

Abstract: Efficient multi-pathway destruction of pollutants is realized over metal-free OVc-CNOP Nfs by PMS activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The D and G bands attributed to the C characteristic peak of the catalyst were clearly affected after the adsorption of the contaminants. A larger I D / I G ration corresponds to an increase in the number of defects, , indicating that BPA is adsorbed on the C center; this is consistent with the DFT calculations. After the Fenton reaction, the ratio returns to the value before the reaction, which proves that the pollutants adsorbed on the electron-poor C­(π) center are gradually degraded.…”
Section: Resultssupporting
confidence: 86%
“…The D and G bands attributed to the C characteristic peak of the catalyst were clearly affected after the adsorption of the contaminants. A larger I D / I G ration corresponds to an increase in the number of defects, , indicating that BPA is adsorbed on the C center; this is consistent with the DFT calculations. After the Fenton reaction, the ratio returns to the value before the reaction, which proves that the pollutants adsorbed on the electron-poor C­(π) center are gradually degraded.…”
Section: Resultssupporting
confidence: 86%
“…A broad diffraction peak of GP@CN was observed at 24.7°, which corresponded to the diffraction peak of the (002) crystal plane of amorphous carbon. 21 After introducing Fe species, a series of prominent diffraction peaks were observed at 35.5°, 40.0°, and 44.7°, which are related to the (311) plane Fe 3 O 4 (PDF 88-0315), (113) plane α-Fe 2 O 3 (PDF 33-0664), 31 and (110) plane Fe 0 (PDF 87-0721), 32,34 respectively, which are consistent with the HRTEM results above. The continuous diffraction peaks in the range 41.0−44.0°contain the Fe 2 N (PDF 76-0090) and Fe 3 N species (PDF 73-2101).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The direct oxidation of organic pollutants by O 2 is often kinetically unfavorable due to the weak oxidation ability of the triplet state of O 2 , which is relatively stable under environmental conditions. Our recent studies have found that the construction of dual-reaction-centers (DRCs), including electron-rich microcenters (ERCs) and electron-poor microcenters (EPCs), on the catalyst surface can greatly induce surface electron transfer and realize the selective reduction of H 2 O 2 , reducing resource and energy consumption and breaking the pH limit. In particular, microactivation (one-electron reduction) of dissolved oxygen (DO) was also observed under natural conditions in an enhanced DRC system based on a Cu-doped graphite polyimide catalyst . The electrons of the pollutants were induced through the DRC-interfacial reaction and finally utilized by DO and H 2 O 2 , realizing the efficient dual-pathway degradation of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The dienol structure of VC exhibits strong reducibility. It can hamper the oxidation of active groups and interrupt the chain reaction during coal oxidation 44,45 . Meanwhile, the MC‐PEG‐SDS solution acts as a VC delivery system, and sol‐gel transition occurs when the temperature is higher than LCST.…”
Section: Resultsmentioning
confidence: 99%
“…It can hamper the oxidation of active groups and interrupt the chain reaction during coal oxidation. 44,45 Meanwhile, the MC-PEG-SDS solution acts as a VC delivery system, and sol-gel transition occurs when the temperature is higher than LCST. Subsequently, VC is wrapped in gel, which avoids VC failure at high temperature and prolongs its release activity.…”
Section: Analysis Of Changes In Gas Compositionmentioning
confidence: 99%